Clonazepam monotherapy for treating people with newly diagnosed epilepsy - Brigo, Francesco (Cochrane Database Syst Rev, 2019)
BACKGROUND: Epilepsy is one of the most common neurological disorders worldwide, with an age‐adjusted prevalence of 4 to 8 per 1000 population and an age‐adjusted incidence of 44 per 100,000 person‐years in developed countries. Monotherapy represents the best therapeutic option in people with newly diagnosed epilepsy. OBJECTIVES: To assess the efficacy and tolerability of oral clonazepam used as monotherapy for newly diagnosed epilepsy, when compared with placebo or a different anti‐seizure medication. SEARCH METHODS: The following databases were searched on 24 July 2018: the Cochrane Register of Studies (CRS Web), which includes the Cochrane Epilepsy Group Specialized Register and the Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE (Ovid) 1946 to 24 July 2018, ClinicalTrials.gov, and the WHO International Clinical Trials Registry Platform (ICTRP). SELECTION CRITERIA: We included randomized controlled trials (RCTs) or quasi‐RCTs comparing oral clonazepam used as monotherapy treatment (where participants were randomized to treatment with a single drug throughout the study period) versus placebo or a different anti‐seizure medication (active comparator) in people of any age with newly diagnosed epilepsy, defined according to the clinical practical definition proposed by the International League Against Epilepsy (ILAE). DATA COLLECTION AND ANALYSIS: The following outcomes were considered: proportion of participants seizure‐free at one, three, six, 12 and 24 months after randomization; proportion of responders (those with at least a 50% reduction in seizure frequency from baseline to end of treatment); proportion of participants with treatment‐emergent adverse events (TEAEs) during the treatment period or leading to discontinuation during the treatment period; proportion of dropouts/withdrawals due to side effects, lack of efficacy or other reasons; and improvement in quality of life, as assessed by validated and reliable rating scales. Two review authors independently screened all titles and abstracts to assess the eligibility of publications identified by the searches. They independently extracted data from trial reports and cross‐checked them for accuracy. Any disagreements between the two authors regarding data extraction were resolved by discussion and consensus. We scrutinized trials and evaluated the methodological quality of all included studies. We used GRADE assessment criteria to evaluate the certainty of the evidence. MAIN RESULTS: Two randomized controlled trials were included, with a total of 115 participants. One study compared clonazepam to carbamazepine as monotherapy for participants with newly diagnosed psychomotor epilepsy (a condition corresponding to what is now termed mesial temporal lobe epilepsy). One study (published as abstract) compared clonazepam to ethosuximide as monotherapy for children with absence seizures. Based on the available data and the details on methodology provided, we judged both studies as being at unclear or high risk of bias for the domains assessed. In the study comparing clonazepam to carbamazepine, no difference was found between the groups regarding the proportion of participants who were seizure‐free at one month after randomization (risk ratio (RR) 1.97, 95% confidence interval (CI) 0.99 to 3.94; 30 participants; very low‐certainty evidence), three months after randomization (RR 1.19, 95% CI 0.62 to 2.29; 26 participants; very low‐certainty evidence), and six months after randomization (RR 0.50, 95% CI 0.09 to 2.73; 9 participants; very low‐certainty evidence). No statistical difference was found between clonazepam and carbamazepine in terms of proportion of participants with TEAEs leading to discontinuation (RR 2.61, 95% CI 0.80 to 8.52; 36 participants; very low‐certainty evidence) and in terms of dropouts/withdrawals due to side effects, lack of efficacy or other reasons (RR 1.56, 95% CI 0.61 to 4.02; 36 participants; very low certainty evidence). The study did not provide any information on our other prespecified outcomes of interest. The study comparing clonazepam to ethosuximide did not provide any data on efficacy. The proportion of dropouts/withdrawal was higher in the group receiving clonazepam compared to the group receiving ethosuximide (RR 3.63, 95% CI 1.12 to 11.74; 79 participants; very low‐certainty evidence). No information on other outcomes of interest was provided in this study. AUTHORS' CONCLUSIONS: There is only limited and very low‐certainty evidence from randomized controlled trials on the efficacy and tolerability of clonazepam used in monotherapy for the treatment of epilepsy. No difference in efficacy and tolerability was found in a small trial comparing clonazepam to carbamazepine for the treatment of mesial temporal lobe epilepsy. Clonazepam was less well tolerated than ethosuximide in a trial of children with absence seizures, however no comparative data on efficacy were provided. There is currently insufficient evidence to support the use of clonazepam as monotherapy treatment for epilepsy.